S-nitrosylation of NF-kB p65 inhibits TSH-induced Na+/I- symporter expression - Nicola, Juan Pablo (2015)
Nitric oxide (NO) is a ubiquitous signaling molecule involved in a wide variety of cellular physiological processes. In thyroid cells, NO-synthase III-endogenously produced NO reduces thyrotropin (TSH)-stimulated thyroid specific gene expression, suggesting a potential autocrine role of NO in modulating thyroid function. Further studies indicate that NO induces thyroid dedifferentiation, as NO donors repress TSH-stimulated I- uptake. Here, we investigated the molecular mechanism underlying the NO inhibited Na+/I- Symporter (NIS)-mediated I- uptake in thyroid cells. We showed that NO donors reduce I- uptake in a concentration-dependent manner, which correlates with decreased NIS protein expression. NO-reduced I- uptake results from transcriptional repression of NIS gene rather than post-translational modifications reducing functional NIS expression at the plasma membrane. We observed that NO donors repress TSH-induced NIS gene expression by reducing the transcriptional activity of the NF-κB subunit p65. NO-promoted p65 S-nitrosylation reduces p65-mediated transactivation of the NIS promoter in response to TSH stimulation. Overall, our data are consistent with the notion that NO plays a role as an inhibitory signal to counterbalance TSH-stimulated NF-κB activation, thus modulating thyroid hormone biosynthesis.